Physicochemical Investigations of Textile Wastewater and Process Parameter Optimization for Bio-decolorization of Congo Red Dye by Pseudomonas aeruginosa MT-2 Strain - Manikant Tripathi; Shivpujan Shukla; Ranjan Singh; Sangram Singh; Pankaj Singh; Pradeep Kumar Singh; Awadhesh Kumar Shukla; Sadanand Maurya; Sukriti Pathak; Vinod Kumar Chaudhary; Ajay Kumar Shukla; R. Manimekalai (Journal of Pure and Applied Microbiology)
Pollution caused by dyes is a major environmental threat, posing adverse impacts on humans, animals, and plants. Therefore, the remediation of such pollutants is essential to protect the environment. This study aimed to conduct physicochemical and bacteriological analyses of textile wastewater to isolate and identify potential native bacterial strains for the decolorization of Congo red dye. Physical and nutritional process parameters were optimized to achieve maximum decolorization. The biological and chemical oxygen demands of the analyzed textile waste water were found to be above the recommended limits. In this study, 19 Congo red -decolorizing bacteria were isolated, with one bacterial culture capable of growing at a higher dye concentration of 300 mg/L. This bacterium was characterized biochemically and genetically (using 16S rRNA sequencing) and identified as the Pseudomonas aeruginosa MT-2 strain. A maximum decolorization of 94.0% was achieved at an initial dye concentration of 150 mg/L, 35°C, and pH 8.0 under static conditions. The bacterial culture also showed resistance to heavy metals such as arsenic, lead, and chromium. The biodegradation of Congo red dye was confirmed through UV-vis spectral analysis and Fourier transform infrared spectrophotometry. The findings of this study demonstrate the high remediation potential of the MT-2 strain, making it suitable for possible use in dye biodecolorization at contaminated sites.